Space utilisation, movement and behaviour of the spiny dogfish, Squalus acanthias, in Macquarie Harbour, Tasmania - David Moreno; Bell, JD; Jeremy Lyle; Jayson Semmens (2016)
Movement and spatial use provide insights into the behaviour of marine organisms which, in turn, enables their effective management. The spiny dogfish, Squalus acanthias, is a common, but vulnerable, shark inhabiting temperate continental shelves circumglobally, yet no information exists on the spatial dynamics of the species in Australia. Twenty-three S. acanthias were implanted with acoustic transmitters and monitored over 1.5 years using a passive acoustic array in Macquarie Harbour, Tasmania. Markov chains and Brownian bridge models were used to analyse the distribution of the species in the harbour. Both males and females displayed non-random site affinity, although the ranges of males changed seasonally. Social association indicated a varying degree of sexual segregation during winter, although patterns were not as clear as reported elsewhere. This represents the first example where the species displays phylopatric behaviour and does not undertake large scale movement. Both sexes are likely to be vulnerable to a variety of anthropogenic impacts within the Harbour and spatial management could be effectively implemented to nullify these impacts. The patterns of space use and behaviours observed in this study are unique for the species. By using random walk models and social networks, it is possible to gain a better understanding of the ways in which S. acanthias has adapted to a seemingly unfit environment.